Montenegro and NATO-Challenges and Perspectives - Saša Knežević (Bezbednosni Dijalozi, 2015)
The foreign policy agenda of Montenegro from the restoration of independence was moving in direction of European and Euro-Atlantic integrations. There was a high level of consensus in the country, especially when it comes to joining the European Union. Montenegro has formally started negotiations with the EU in late July 2012 and now is at the doorstep of NATO bearing in the mind the commitment to contribute to the preservation of peace at the regional and global level. Montenegro in July 2009 made a decision to engage the army representatives in the ISAF mission in Afganistan. The officials expect the invitation for membership in NATO to the end of this year, but it is more evident that not everything in this story depends on Montenegro.